Tremor-Dominant in Parkinson Disease: The Relevance to Iron Metabolism and Inflammation - Lian, Teng-Hong; Guo, Peng; Zuo, Li-Jun; Hu, Yang; Yu, Shu-Yang; Yu, Qiu-Jin; Jin, Zhao; Wang, Rui-Dan; Li, Li-Xia; Zhang, Wei (Frontiers in Neuroscience, 2019)
Background Tremor is one of the most predominant symptoms of patients with Parkinson disease (PD), but the underlying mechanisms for tremor relating iron and its metabolism-related proteins and the inflammatory factors in cerebrospinal fluid (CSF) and serum have not been fully elucidated. Methods A total of 135 PD patients were divided into tremor-dominant (PD-TD) group (N=74) and gait difficulty-dominant (PD-PIGD) group (N=39) based on the ratio of mean tremor score to the mean bradykinesia/rigid score in Unified Parkinson's Disease Rating Scale (UPDRS) III. Age and sex-matched healthy controls were recruited (N=35). Demographic variables were evaluated; iron and its metabolism-related proteins and the inflammatory mediators in both CSF and serum were measured in these groups. The relevance of iron metabolism, inflammation and PD-TD were analyzed. Results 1. PD-TD group had significantly decreased L-ferritin, increased iron levels in CSF and increased ferritin level in serum compared with PD-PIGD and control groups (P<0.05). PD-TD was prominently and positively correlated with iron level (r=0.345, P=0.011) and negatively correlated with L-ferritin level (r=-0.831, P=0.022). 2. PD-TD group had significantly enhanced IL-6 levels in both CSF and serum compared with PD-PIGD and control groups (P<0.05). IL-6 levels in both CSF and serum were positively and significantly correlated with PD-TD (r=0.313, P=0.048，r=0.276, P=0.028, respectively). 3. In CSF, IL-6 level was increased as iron level was elevated in PD-TD group (r=0.308, P=0.022). In serum, IL-6 level was increased as ferritin level was elevated in PD-TD group (r=0.410, P=0.004). Conclusions The interplay between disturbed iron metabolism and relevant inflammation might modulate clinical phenotypes of PD.